Approach to arthritis: An overview (Research, Society and Development, 2023)
Objective: To review the approach and management of patients with arthritis. Methodology: This is a narrative review, carried out through searches on the PubMed platform, using the descriptors "Arthritis", "Monoarthritis" and "Polyarthritis". Studies available in full in English or Portuguese were included. Publications that did not meet the inclusion criteria or the scope of the topic were excluded, resulting in the selection of 40 studies. Chapters from reference books in Rheumatology were added to complement the information extracted from the articles. Results and Discussion: Arthritis is classified according to the characteristics of the pain, time of evolution, symmetry, number, location, size of the joints involved and temporality. Anamnesis of a patient with arthritis requires investigation of the epidemiological profile and personal and family medical history. The physical examination requires inspection, palpation, passive and active movement and special maneuvers. The main causes of monoarthritis are crystal-induced arthritis, septic arthritis and trauma, and arthrocentesis with synovial fluid study may be necessary for diagnostic elucidation. Among oligoarthritis, gonococcal arthritis and spondyloarthritis stand out, while polyarthritis is more associated with viral conditions, rheumatoid arthritis, collagenosis and spondyloarthritis. Complementary exams can help with diagnosis, follow-up and prognosis, and need to be directed according to the diagnostic hypotheses. Conclusion: The study of arthritis is of great importance, given its high prevalence and morbidity, requiring a detailed anamnesis and physical examination.